2004
DOI: 10.1590/s1415-65552004000100002
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do impacto dos sistemas ERP sobre variáveis estratégicas de grandes empresas no Brasil

Abstract: O artigo apresenta os resultados de uma pesquisa survey realizada numa amostra das 500 melhores e maiores empresas do Brasil, de acordo com a classificação da Revista Exame (2000). A pesquisa procurou avaliar o impacto da utilização dos sistemas ERP (Enterprise Resource Planning) ou Sistemas Integrados de Gestão, sobre as variáveis estratégicas dessas organizações. O instrumento de coleta de dados é uma adaptação do original criado por Mahmood e Soon (1991), para avaliação do impacto da Tecnologia da Informaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
23

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 8 publications
1
3
0
23
Order By: Relevance
“…Caldas & Wood Jr. (2000) also studied ERP in Brazil and their research indicates that many companies did not perceive improvements in customer service. Saccol et al (2004) highlight that the main contribution of ERP systems is related to productivity and efficiency gains (both confirmed in our research). Therefore we can conclude that the main consequences of the non-mobile ERP have similarity with those of mobile ERP.…”
Section: Company Three -This Company Was Founded In 2008 and It Has 20supporting
confidence: 88%
See 1 more Smart Citation
“…Caldas & Wood Jr. (2000) also studied ERP in Brazil and their research indicates that many companies did not perceive improvements in customer service. Saccol et al (2004) highlight that the main contribution of ERP systems is related to productivity and efficiency gains (both confirmed in our research). Therefore we can conclude that the main consequences of the non-mobile ERP have similarity with those of mobile ERP.…”
Section: Company Three -This Company Was Founded In 2008 and It Has 20supporting
confidence: 88%
“…The first one is related to possible consequences of ERP use for communication and relationships with customers and suppliers. Previous researches such as Saccol et al (2004) indicated a little impact of (non-mobile) ERP in the strategic variables clients and suppliers. Caldas & Wood Jr. (2000) also studied ERP in Brazil and their research indicates that many companies did not perceive improvements in customer service.…”
Section: Company Three -This Company Was Founded In 2008 and It Has 20mentioning
confidence: 95%
“…Entretanto, Saccol et al (2004) afirmam que o sistema ERP contribui pouco com os fatores estratégicos referentes aos clientes e consumidores, à rivalidade competitiva e ao mercado. Ele contribui mais fortemente com a eficácia organizacional, pois está ligado com a gestão de fornecedores e ganhos de produtividade, facilitando a gestão e integrando a comunicação intraorganizacional e também a externa.…”
Section: Erp (Enterprise Resource Planning)unclassified
“…Essa sugestão foi atendida, pois a estrutura definida tem de um a sete critérios no nível mais baixo de cada grupo de critérios e quatro alternativas identificadas. Em relação aos critérios para a escolha de um sistema ERP, pode-se perceber que os critérios realmente visam a uma eficiência organizacional (SACCOL et al, 2004) e à facilidade na implantação (MERODE et al, 2004).…”
Section: 32unclassified
“…O estudo sobre o impacto da adoção de tecnologias de informações pelas organizações é pauta de pesquisas acadêmicas de longa data, a exemplo do estudo clássico de Venkatesh et al (2003), dos estudos nacionais de Maçada e Becker (2001), Freitas e Rech (2003), Saccol et al (2004), entre outros. Mais recentemente, com o crescimento das TIMs, novas questões emergem com relação ao seu impacto no contexto organizacional, tendo em vista o potencial de mudança que essas novas tecnologias podem trazer ao trabalho diário, à medida que questões de tempo e lugar caem por terra (DAVIS, 2002;CORSO;BEHR, 2011 e MARQUES;JOÃO, 2003;JEDDI, 2014).…”
Section: Considerações Finais E Direcionamentos Para Estudos Futurosunclassified